Atypical astroglial pTDP‐43 pathology in astroglial predominant tauopathy. (2nd April 2021) - Gelpi, Ellen; Aldecoa, Iban; Lopez‐Villegas, Dolores; Abellan‐Vidal, Maria Teresa; Mercadel‐Fañanas, Pilar; Fortea, Juan; Ribosa, Roser; Morenas, Estrella; Gomez‐Anson, Beatriz; Molina‐Porcel, Laura; Ximelis, Teresa; Borrego, Sergi; et al.
Abstract : We observed atypical astrocytic pTDP‐43 pathology in astroglial predominant tauopathy.